2021
DOI: 10.4103/joacp.joacp_358_19
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal nebulization of ropivacaine for control of pain after laparoscopic cholecystectomy -A randomized control trial

Abstract: Background and Aims: Use of high dose opioids following laparoscopic surgery delays discharge from the hospital. Unlike intraperitoneal instillation, nebulization has been reported to provide a homogeneous spread of local anesthetics and provide better analgesia. In our study, we aimed to assess the efficacy of intraperitoneal nebulization of local anesthetic in alleviating postoperative pain in patients undergoing laparoscopic cholecystectomy. Material and Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…El caso que reportamos no mostró dolor referido al hombro durante su estancia hospitalaria. Marta Somaini y colegas, Sai Sandhya y equipo nebulizaron ropivacaína 4 mL al 0.75% (3 mg) antes del inicio de la cirugía, obteniendo resultados favorables (11,12) . A pesar de que no existe actualmente un momento ideal de administración, nosotros nebulizamos al final del procedimiento, debido a que consideramos que la bruma que genera en la cavidad condiciona poca visibilidad de estructuras, lo cual ocasiona dificultad para el cirujano.…”
Section: Discussionunclassified
“…El caso que reportamos no mostró dolor referido al hombro durante su estancia hospitalaria. Marta Somaini y colegas, Sai Sandhya y equipo nebulizaron ropivacaína 4 mL al 0.75% (3 mg) antes del inicio de la cirugía, obteniendo resultados favorables (11,12) . A pesar de que no existe actualmente un momento ideal de administración, nosotros nebulizamos al final del procedimiento, debido a que consideramos que la bruma que genera en la cavidad condiciona poca visibilidad de estructuras, lo cual ocasiona dificultad para el cirujano.…”
Section: Discussionunclassified
“…Tramadol consumption was lower, with a statistically significant difference at 24 hours (P = 0.044). That study showed that intraperitoneal nebulization of ropivacaine was both effective and safe in providing postoperative analgesia in LC [ 10 ]. Similar results have been reported in other studies [ 11 12 ].…”
Section: Discussionmentioning
confidence: 99%